Extraction Efficiency of Dry-Hopping. (3rd July 2019) - Hauser, Dean G.; Lafontaine, Scott R.; Shellhammer, Thomas H.
Abstract: Dry-hopping, which is the cold, aqueous extraction of hops into beer, has gained popularity in recent years as a method for achieving intense hop aroma and flavor in beer. With some brewers dry-hopping at rates up to 2 kg/hL (∼5 lb/barrel), considerable waste is generated in terms of both beer loss and spent hops. The retention of valuable volatile and non-volatile hop components within spent hops, as well as their extraction into beer, was investigated on both a pilot and industrial scale. On the pilot scale (80 L), an unhopped pale ale was statically dry-hopped with differing lots of whole cone Amarillo ®, Centennial, and Cascade at a rate of 386 g/hL (1 lb/bbl) for 24 h at 13 °C (55 °F). Spent hop material was also collected from a local brewery that dry-hopped ∼60 hL (50 bbl) of beer at a rate of 1, 592 g/hL (4.125 lb/bbl). Approximately one-third of the dry-matter composition of hops was lost during dry-hopping regardless of hop variety; however, there was high retention of both α-acids (77% pilot scale, 52% industrial) and hop essential oil (51% pilot scale, 33% industrial). The oil remaining in the spent hops was enriched in hydrocarbon compounds and depleted in oxygenated compounds. These results indicate that spent dry-hops contain considerable brewing value and have the potential for re-use.